The Influence of Democratic Leadership Style on Employee Performance at the Watang Sawitto District Office Pinrang - Suprianto Suprianto; Dwi Wahyuni Taufiq; Asmilah Abdullah; Usniar Usniar; Hasriah Hasriah (Jurnal Office, 2021)
An organization, to improve employee performance depends on the leadership style itself. This study aims to determine the effect of democratic leadership style on employee performance at the Watang Sawitto District Office, Pinrang Regency. This research is quantitative research that shows a causal relationship. The population in this study was 31. Data collection techniques used are observation, questionnaires, interviews, and documentation. The data analysis technique used is a descriptive statistical analysis using percentages and inferential statistical analysis using data normality tests, product-moment correlation analysis, and simple linear regression analysis. The results showed that the democratic leadership style at the Watang Sawitto District office, Pinrang Regency was in the very good category in terms of decisions made together, respecting the potential of subordinates, listening to criticism, suggestions, and opinions from subordinates, and cooperating with subordinates. Meanwhile, employee performance is in the very good category in terms of service orientation, commitment, work initiative, cooperation, and leadership. Based on simple linear regression analysis, it shows that democratic leadership style influences employee performance. This research can be used as a reference that focuses on the democratic leadership style on employee performance because the previous research focused on employee work motivation.